Stereotactic Body Radiotherapy (SBRT) for Oligometastatic Spine Metastases: An Overview - Zeng, Kang Liang; Tseng, Chia-Lin; Soliman, Hany; Weiss, Yonatan; Sahgal, Arjun; Myrehaug, Sten (Frontiers in Oncology, 2019)
The oligometastatic state is hypothesized to represent an intermediary state of cancer between widely metastatic disease and curable, localized disease. Advancements in radiotherapy have allowed for delivery of high precision, dose escalated treatment known as stereotactic body radiotherapy (SBRT) to targets throughout the body with excellent rates of local control. Recently, the first phase II randomized trial comparing conventional radiotherapy to comprehensive SBRT of oligometastatic disease demonstrated an overall survival and progression free survival advantage. The spine is a common site of metastasis, and a complex site for SBRT given the adjacent spinal cord and the tumor embedded within the bone tissue putting the patient at risk of fracture. Although there are expert spine SBRT guidelines for practice, there are as yet no reported randomized trials that proves superiority as compared to conventional radiation. The use of SBRT in patients with oligometastatic disease and spinal metastases is the focus of this review.